Determination of smoke layer interface height of medium scale tunnel fire scenarios. (June 2016) - Gao, Z.H.; Ji, J.; Fan, C.G.; Li, L.J.; Sun, J.H.
Highlights: A buoyancy frequency method is proposed based on the vertical stratification of density. A set of burning experiments were conducted in a physical tunnel model. The thermal layer thicknesses determined by different methods are compared with each other. The accuracy and applicability of buoyancy frequency method has been validated. The limitation of integral ratio method and the N -percentage rule are also discussed. Abstract: Smoke layer interface height is an important parameter in fire safety science. In this paper, a series of experiments were conducted in a 1/6th scale model tunnel for determining the smoke layer interface height in medium scale tunnel fire scenarios. The commonly used approaches, including visual observation, N -percentage rule and integral method are reviewed firstly. Then, considering the subjectivity and empiricism of previous approaches, a buoyancy frequency method is put forward based on the vertical temperature distribution in tunnel, which has definite physical meaning and eliminates the subjectivity of previous methods. The smoke layer thicknesses determined by buoyancy frequency method are compared with the results of visual observation, N -percentage rule ( N = 10, 20, 30) and integral ratio method, respectively. The comparison results reveal that the smoke layer thicknesses determined by buoyancy frequency method fit best with the visual values for all the experimental conditions. While the calculated values by integral ratio method are lower than the visual values. In addition, the selection of optimum N values for the N -percentage rule in different cases is also discussed.